Energizing solar still efficiency with eco-friendly coconut shell biochar enhanced organic phase change material - Rajamony, Reji Kumar; Suraparaju, Subbarama Kousik; Kalidasan, B.; Yadav, Aman; Kumar Pandey, Adarsh Kumar; Nurhanis Sofiah, Abd Ghafar; Siaw Paw, Johnny Koh; Fatehmulla, Amanullah; Samykano, Mahendran; Saidur, Rahman Md (Elsevier B.V., 2025)
Solar stills (SS) have emerged as a viable solution to water scarcity, particularly in isolated or rural areas where access to clean water is limited. These systems utilize solar energy for the processes of evaporation and condensation, offering a sustainable and environmentally friendly method for water purification. However, the primary drawback of conventional SS lies in its relatively low production capacity, constrained by daylight hours and limited thermal efficiency. This study presents an innovative advancement by incorporating coconut shell biochar-enhanced phase change materials (CSePCM) into solar stills. The novelty of this approach lies in the integration of CSePCMs, which significantly improve the thermal performance of the system, addressing both energy efficiency and production limitations inherent in traditional SS technologies. A comprehensive characterization of the CSePCM materials was conducted, evaluating their morphological structure, elemental composition, chemical stability, thermal conductivity, and melting enthalpy. Experimental results demonstrated that the CSePCM-3 variant enhanced thermal conductivity by 88.64%, optical performance by 80.77%, and melting enthalpy by 11.54% compared to the baseline phase change materials. These improvements resulted in notable performance gains for the integrated SS system, with water temperature, absorber temperature, and distillate production increasing by 10.1%, 8.2%, and 72.7%, respectively, relative to conventional SS. Furthermore, cost analysis revealed that the SS-CSePCM system offers a 34.63% reduction in production costs and a 43.58% faster payback period. These findings underscore the scalability and practical applicability of the proposed system, positioning it as a sustainable, cost-efficient, and adaptable solution for clean water production in water-scarce regions globally.